The effects of pre-cooling on performance, pacing strategy and contractile function during endurance cycling in the heat - Duffield, R.; Green, R.; Castle, P.; Maxwell, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction: The reduction in exercise performance noted when performing prolonged exercise in the heat is well documented (Gonzalez-Alonso et al., 1999). Further, the ergogenic benefits of pre-cooling prior to exercising in hot conditions are also well established (Marino 2002). However, to date the mechanisms underlying the improved performances following pre-cooling in the heat remain equivocal. Accordingly, this study investigated the effects of pre-cooling on performance and pacing during free-paced endurance cycling in the heat, and further, the effects of pre-cooling on contractile function as a mechanism for performance improvement. Methods: Following familiarisation, eight male cyclists performed two randomised 40-min time trials on a cycle ergometer (SRM power cranks) in 33oC. Prior to the time trials, participants underwent either a 20-min lower-body cold-water immersion procedure (14oC) or no cooling intervention. Prior to and following the respective intervention and time trial, 10 x 5 s isometric voluntary force (MVC) and evoked twitch force (Pf), muscle temperature and anaerobic blood metabolites were measured. Further, before, during and following the intervention and time trial, measures of core (rectal) and skin temperature and heart rate were recorded. Results: Results indicated that performance was improved with pre-cooling, with a greater distance covered (19.3±1.3 v 18.0±1.4 km) and a higher mean power output maintained (198±25 v 178±26 W) for pre-cooling and control, respectively (P=0.05). While core, muscle, skin and mean body temperatures were lower in the cooling condition until the 20th min (P<0.05), performance did not differ until the latter parts of the time trial (29th min), by which time no differences in physiological measures were present. Further, while MVC was reduced post-exercise in both conditions, neither MVC nor Pf were different between conditions pre- or post-exercise. Discussion: A 20-min lower-body pre-cooling intervention improved free-paced endurance exercise; however, the improvements in performance became evident after physiological differences induced by pre-cooling had dissipated. Further, rather than pre-cooling increasing power output per se, it seems pre-cooling prevented the reduction in self-selected exercise intensity noted in the final 10-min during exercise without cooling. Moreover, the lack of difference between conditions in MVC or the change in Pf indicates improvements in performance did not result from the prevention of interference of voluntary or evoked contractile function, suggesting cooling induced improvements may result from mechanisms related to muscle recruitment and/or activation.